Quantitative Evaluation for PMPIv6 Multicast Fast Reroute Operations - Aisha-Hassan A. Hashim; Azana Hafizah Mohd Aman; Huda Adibah Mohd Ramli (Institute of Advanced Engineering and Science, 2017)
This paper evaluates Proxy Mobile Internet Protocol Version 6 (PMIPv6) multicast fast reroute operations using quantitative analysis. The motivation is to cater the fast growth of mobile data traffic consumption and its networking technologies. Hence it is significance to enhancing the present techniques. Multicast enabled PMIPv6 is a mobile multicast networking management protocol that is highly acceptable in handling mobile data traffic. This paper briefly highlights the methodology, architecture and processes involved to produce the quatitative equations for each parameter. The quantitative parameters discussed are packet loss cost and handover latency.